2015
DOI: 10.18632/oncotarget.5878
|View full text |Cite
|
Sign up to set email alerts
|

Dual mTOR inhibitor MLN0128 suppresses Merkel cell carcinoma (MCC) xenograft tumor growth

Abstract: Merkel cell carcinoma (MCC) is an aggressive neuroendocrine skin cancer. Pathologic activation of PI3K/mTOR pathway and elevated expression of c-Myc are frequently detected in MCC. Yet, there is no targeted therapy presently available for this lethal disease. Recently, MLN0128, a second-generation dual TORC1/2 inhibitor is shown to have therapeutic efficacy in preclinical studies. MLN0128 is currently in clinical trials as a potential therapy for advanced cancers. Here we characterize the therapeutic efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 71 publications
(113 reference statements)
1
23
1
Order By: Relevance
“…Combined with our previous findings that the upregulation of phosphorylated IκB induced by GOS is associated with NF-κB nuclear translocation 20 , we speculated that Akt phosphorylation contributes to GOS-stimulated signalling. In addition, the Akt/mTOR signalling pathway is reported to participate in various processes, including cell growth, autophagy, apoptosis and immune regulation 27 , and activated Akt was found to induce expression of IL-6, TNF-α and IL-12 by initiating phosphorylation of mTOR and p70 S6K 28 . According to current findings (Figs 2D,E and 3), we propose that GOS-mediated immune regulation in RAW264.7 macrophages is divided into the following major steps: (1) GOS the surface receptor TLR4; (2) PI3K is activated by TLR4 and subsequently induces Akt phosphorylation; (3) phosphorylated Akt triggers IκB phosphorylation, resulting in (4) the release and translocation of NF-κB into the nucleus; (5) mTOR and p70 S6K are also activated by p-Akt; (6) all these factors work together or separately to induce the production of inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with our previous findings that the upregulation of phosphorylated IκB induced by GOS is associated with NF-κB nuclear translocation 20 , we speculated that Akt phosphorylation contributes to GOS-stimulated signalling. In addition, the Akt/mTOR signalling pathway is reported to participate in various processes, including cell growth, autophagy, apoptosis and immune regulation 27 , and activated Akt was found to induce expression of IL-6, TNF-α and IL-12 by initiating phosphorylation of mTOR and p70 S6K 28 . According to current findings (Figs 2D,E and 3), we propose that GOS-mediated immune regulation in RAW264.7 macrophages is divided into the following major steps: (1) GOS the surface receptor TLR4; (2) PI3K is activated by TLR4 and subsequently induces Akt phosphorylation; (3) phosphorylated Akt triggers IκB phosphorylation, resulting in (4) the release and translocation of NF-κB into the nucleus; (5) mTOR and p70 S6K are also activated by p-Akt; (6) all these factors work together or separately to induce the production of inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically targeting both mTOR complex 1 and complex 2, the dual mTOR inhibitor, MLN0128, was able to inhibit MCC xenograft tumor growth in vivo [75]. A phase I dose escalation protocol of MLN0128 is expected to complete imminently [76], and a phase II trial for patients with advanced MCC has just begun recruiting patients [77].…”
Section: Emerging Treatmentsmentioning
confidence: 99%
“…Meanwhile, BIIB021 results in death of chronic myeloid leukemia cells through regulation of mTOR-Ulk1 signal pathway [23]. In regard to involvement of mTOR in cell survival, it was reported that the dual mTOR inhibitor MLN0128 inhibited tumor growth in Merkel cell carcinoma-xenograft model [29]. In this study, BIIB021 reduced expression of total and phospho-Akt, denoting the impediment of phosphorylation as well as expression of Akt by BIIB021.…”
Section: Discussionmentioning
confidence: 62%